Karakteristik Dukun Bersalin Tentang Kemitraan dengan Bidan di Wilayah Puskesmas Mataraman Kabupaten Banjar - Akhmad Mahyuni; Sugeng Riyanto; Novita Hendrawati; STIKES Husada Borneo; Alumni STIKES Husada Borneo (HB PRESS, 2014)
Traditional birth attendant is a woman who has the ability to perform the help of labor obtained with traditional methods. Partnership, cooperation based on mutual agreements between the parties concerned. The specific aims of this research are: to determine the characteristics of a traditional birth attendant in work of Puskesmas Mataraman, to determine a traditional birth attendant about partnership with midwives in area of Puskesmas Mataraman, and to determine the characteristics of a traditional birth attendant about partnership with midwives in area of Puskesmas Mataraman. This study used a descriptive method is a method of research conducted with the main objective to description of a situation objectively. This study used cross sectional approach and the sampling technique used in the total population that is sample in this research all a traditional birth attendant are located in area of Puskesmas Mataraman amounted to 22 people. Data collection techniques are obtained from direct interviews with questionnaires to the respondents. From the results of this research obtained the majority of education by the respondent only basic level or elementary level (90.91%), the largest age group of respondents is the age group 50-54 years (27.28%) and the highest level of respondents' knowledge obtained is lack of knowledge level (63.64%). Based on the research that has been done it is recommended to health institutions to provide refreshment to the health workers, especially midwives toward mother and child health for handling cases of births attended by a traditional birth attendant.